Reproduction of Gerres cinereus (Percoidei: Gerreidae) off the Mexican Pacific coast - Espino-Barr, Elaine; Gallardo-Cabello, Manuel; Cabral-Solís, Esther G.; Puente-Gómez, Marcos; García-Boa, Arturo (Revista Ciencias Marinas y Costeras, 2015)
Yellowfin Mojarra Gerres cinereus (Walbaum, 1792) off the Mexican Pacific coast is a popular low-cost species, which is caught with gill and cast nets. Knowing breeding seasons, gonadal maturity, fecundity and size at sexual maturity is necessary for fishery management. Samples were obtained from April 2010 to November 2011. Size, sex and gonad maturity were recorded, while the gonadosomatic index and the fecundity and condition factors were calculated using the gravimetric method. To calculate this information by age, growth parameters previously published were used. The female:male ratio was 1:1.024. Mature females were observed year round with two major peaks during July and October. Sexual maturation (L0.5) of males and females was 16.40 cm and 20.20 cm, respectively, corresponding to one-year old organisms. First maturity length (L0.25) was 15.80 cm in males and 16.50 cm in females. The hepatosomatic index vs length was LW = 2.00·10-6 ·TL4.213, resulting in a positive allometric relationship. Condition factor indexes increased during February and September. Average oocyte diameter was 0.31 mm (0.15 to 0.45 mm). Fecundity ranged from 37,784 to 1,746,510 oocytes in females from one to seven years of age, and mean relative fecundity was 1332 oocytes·g-1 (294 to 4,430 oocytes·g-1). G. cinereus has an early sexual maturity, reproduces once or twice a year and has a high fecundity rate, which allows it to be caught all year round, if caught after the first maturity length.